Best practice interprofessional stroke care collaboration and simulation: The student perspective. Issue 6 (2nd November 2017) - MacKenzie, Diane; Creaser, Gail; Sponagle, Kim; Gubitz, Gordon; MacDougall, Peter; Blacquiere, Dylan; Miller, Stephen; Sarty, Gordon
ABSTRACT: Interprofessional practice (IPP) is the accepted standard of care for clients following a stroke. A brief, embedded and evidence-based IPP team simulation was designed to address stroke care knowledge and IPP competencies for students within limited curriculum space. Each team was required to construct a collaborative care plan for their patient during the simulation and submit the care plan for evaluation of best practice stroke care knowledge and implementation with evidence of interprofessional collaboration (IPC). A total of 302 students (274 on-site, 28 by distance technology) representing four professions comprised of 55 teams took part in this experience. Post-simulation, voluntary and anonymous programme evaluations were completed using the standardised interprofessional collaborative competency assessment scale (ICCAS) and open-ended free-text responses to five questions. There was a significant improvement for all pre–post ratings on the ICCAS regardless of profession or previous interprofessional experience. Additionally, the open-ended responses indicated perceived changes to role clarification, communication, and teamwork. The combined interpretation of the programme evaluation results supports interprofessional team simulation as an effective and efficient learning experience for students regardless of previous interprofessional experience, and demonstrated positive changes in stroke best-practice knowledge and IPC competencies.